Seroprevalence of anti-SARS-CoV-2 antibodies among school and daycare children and personnel: protocol for a cohort study in Montreal, Canada. Issue 7 (8th July 2021) - Zinszer, Kate; McKinnon, Britt; Bourque, Noémie; Zahreddine, Monica; Charland, Katia; Papenburg, Jesse; Fortin, Geneviève; Hamelin, Marie-Ève; Saucier, Adrien; Apostolatos, Alex; Pierce, Laura; Savard-Lamothe, Ashley; et al.
Abstract : Introduction: Further evidence is needed to understand the contribution of schools and daycares for the spread of COVID-19 in the context of diverse transmission dynamics and continually evolving public health interventions. The Enfants et COVID-19: Étude de séroprévalence (EnCORE) study will estimate the seroprevalence and seroconversion of SARS-CoV-2 among school and daycare children and personnel. In addition, the study will examine associations between seroprevalence and sociodemographic characteristics and reported COVID-19 symptoms and tests, and investigates changes in health, lifestyle and well-being outcomes. Methods and analysis: This study includes children and personnel from 62 schools and daycares in four neighbourhoods in Montreal, Canada. All children aged 2–17 years attending one of the participating schools or daycares and their parents are invited to participate, as well as a sample of personnel members. Participants respond to brief questionnaires and provide blood samples, collected via dried blood spot, at baseline (October 2020–March 2021) and follow-up (May–June 2021). Questionnaires include sociodemographic and household characteristics, reported COVID-19 symptoms and tests, potential COVID-19 risk factors and prevention efforts and health and lifestyle information. Logistic regression using generalised estimating equations will be used to estimate seroprevalence and seroconversion, accounting for school-level clustering. Ethics and dissemination: This study was approved by the research ethics boards of the Université de Montréal (CERSES) and the Centre Hospitalier Universitaire Sainte-Justine. Results will contribute to our knowledge about SARS-CoV-2 transmission in schools and daycares and will be made available to study participants and their families, school and public health decision-makers and the research community.